Improved photovoltaic performance of dye‐sensitized solar cells using dual post treatment based on TiCl4 and urea solution. (20th January 2021) - Bolag, Altan; Wang, Qiaoling; Liu, Linan; Jamiyansuren, Tumenkhuslen; Tumurpurev, Ugtakhbayar; Tuvjargal, Norovsambuu; Bao, Tana; Ning, Jun; Alata, Hexig; Tegus, Ojiyed
Abstract: An effective and efficient photovoltaic performance is significantly affected by the interface between different constituents of dye sensitized solar cells (DSSC). A novel dual post treatment of TiCl4 and urea solutions on different layers of TiO2 electrode is addressed and the TiO2 particle morphology, dye‐adsorption amount on the TiO2 electrode and the photovoltaic performance of the DSSC based on those electrodes are characterised in this work. TiCl4 treatment can form more binding site on TiO2 particles and urea treatment structures a thin layer of g‐C3 N4 on the surface of TiO2 particles. This strategy can not only effectively increase the dye‐adsorption for light‐harvesting, but also facilitate the electron transfer through inhibiting the charge recombination between TiO2 and electrolyte, and moreover, it provides excess electrons for the photoanodes. The DSSC fabricated from TiO2 electrode processed with urea treatment on the sixth layer exhibited the highest power conversion efficiency of 8.94% with a short current density J sc of 24.09 mA cm –2, an open circuit voltage V oc of 583 mV and a fill factor of 63.8.